Association between estimated pulse wave velocity and the risk of stroke in middle-aged men. Issue 5 (July 2021) - Jae, Sae Young; Heffernan, Kevin S; Kurl, Sudhir; Kunutsor, Setor K; Laukkanen, Jari A
Background: Increased aortic stiffness, assessed as carotid-femoral pulse wave velocity (cfPWV), contributes to cerebrovascular damage and is predictive of cerebrovascular events. Aims and methods: We sought to examine the association between estimated pulse wave velocity (ePWV), a proxy of carotid-femoral pulse wave velocity, and stroke and its subtypes (ischemic and hemorrhagic) in a prospective cohort of 2666 men (aged mean 53.1, range 42–61 years) enrolled in the Kuopio Ischemic Heart Disease cohort study. Results: During a median 28-year follow-up, 471 incident stroke (397 ischemic and 94 hemorrhagic) events occurred. After adjusting for several established and emerging risk factors including age and pulse pressure, comparing the p versus bottom quartiles of ePWV, there was an increased risk of stroke (hazard ratio [HR] 2.37, 95% Confidence Interval [CI]: 1.57–3.58), ischemic stroke (HR 2.23, 95% CI, 1.42–3.50), and hemorrhagic stroke (HR 3.57, 95% CI, 1.45–8.76). Conclusion: These findings demonstrate that ePWV is independently associated with the risk of stroke in middle-aged men.